Measuring the perceptions of prospective teachers: Planning technology-based learning during the Covid-19 pandemic - Sudaryanto, Memet; Zainudin, M. (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Online learning planning presents unique challenges that aspiring teachers must prepare for. This study aims to identify potential teachers' perspectives on designing technology-based instruction. Competency dimensions were created based on the findings of focused group discussions (FGD) with teachers and lecturers, which resulted in aspects of social networking, managing digital identity, filtering, creating content, and reusing. Following the FGD, indicators of nine dimensions"”pre-learning, opening planning, material mastery, learning models, learning resources, student involvement, assessment of processes and results, interaction mastery, and closing learning"”were created. Samples were taken through simple random sampling of 250 prospective teachers in education study programs at Jenderal Soedirman University, Sebelas Maret University, IKIP PGRI Bojonegoro, PGRI University Yogyakarta, and Surabaya State University. From these competencies, construction testing through confirmatory factor analysis shows a chi-s Square of 1063.59 with df= 32 (required criteria for chi-s Square < 2df), p-value 0.000 (required criteria â‰¥ 0.05), even though the Root value of the Mean Square Error of Approximation (RMSEA) has met the required criteria of â‰¤ 0.08, namely 0.072. Testing on the measurement model generated 32 items and nine indicators of prospective teachers' perceptions of planning technology-based learning. The four competencies of pre-learning, planning to open learning, and closing learning have the highest scale of abilities attained. The learning resources and media created by future teachers have the lowest aptitude.